Analisis Trend Global Suhu Permukaan Laut (SST) Filipina Menggunakan Data Penginderaan Jauh - Rizfariansyah, Muhammad; Hadi Hayyan, Raihan; D. Hariyanto, Yosafat (Program Studi Ilmu Kelautan, Jurusan Perikanan dan Ilmu Kelautan, Fakultas Pertanian, Universitas Mataram, 2025)
This study aims to analyze global Sea Surface Temperature (SST) trends using remote sensing data over the past two decades. The primary focus of this study is the Western Pacific region, particularly around the Philippines, which is known as a key area for tropical cyclone development. The methodology includes data collection from reliable remote sensing sources, data processing, and temporal and spatial analysis to identify patterns of SST changes and anomalies. The expected outcomes of this research include a better understanding of SST trends, the identification of warming hotspots, and contributions to global climate studies. This study is expected to provide significant insights into the impacts of climate change on marine ecosystems and weather patterns, as well as support the development of mitigation and adaptation strategies for climate change.